Advanced Polymers in Medicine 2014
DOI: 10.1007/978-3-319-12478-0_7
|View full text |Cite
|
Sign up to set email alerts
|

Polymers in Tissue Engineering

Abstract: The landscape of polymer selection and processing techniques is constantly evolving in the field of tissue engineering and regenerative medicine. This chapter will cover new advances in polymers that are used to regenerate functional tissues used to repair or replace tissues lost to age, disease, injury, or congenital defect. The focus will be on new processing techniques and the incorporation of biologics or drug delivery to enhance cellular response and ingrowth into the polymers that will create a more func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 161 publications
(209 reference statements)
0
2
0
Order By: Relevance
“…This indicated that Alphastatin played a part in the ionic cross-linking. In a strict definition, the particle size of the nanomaterial should be between 1 and 100 nm [16], but the diameter of the nanoparticles made by polymer material may be larger than 100 nm, ranging from 10 to 500 nm, and cannot exceed 1000 nm [17]. In this study, AsCs NPs at the mass ratio of 2 : 1 were still nanoparticles since their average particle size was 387 4 ± 12 5 nm.…”
Section: The Effect Of the Cs/alphastatin Ratio On Characteristicsmentioning
confidence: 81%
“…This indicated that Alphastatin played a part in the ionic cross-linking. In a strict definition, the particle size of the nanomaterial should be between 1 and 100 nm [16], but the diameter of the nanoparticles made by polymer material may be larger than 100 nm, ranging from 10 to 500 nm, and cannot exceed 1000 nm [17]. In this study, AsCs NPs at the mass ratio of 2 : 1 were still nanoparticles since their average particle size was 387 4 ± 12 5 nm.…”
Section: The Effect Of the Cs/alphastatin Ratio On Characteristicsmentioning
confidence: 81%
“…[6, 13] Our method for creating these fibers can utilize a variety of photosensitive polymers which can be robust and tuned for biodegradability. [14] Here we demonstrate the patterning of HeLa cells in poly(ethylene glycol) diacrylate (PEGDA) and methacrylated gelatin (GelMA) [15] solutions, and confirm high cell viability after fiber extraction.…”
mentioning
confidence: 79%